2009
DOI: 10.1002/jcu.20569
|View full text |Cite
|
Sign up to set email alerts
|

Endometriomas in the region of a scar from Cesarean section: Sonographic appearance and clinical presentation vary with the size of the lesion

Abstract: LSEs were associated with a delay in diagnosis and some US findings that could result in further diagnostic difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
4
24
1
Order By: Relevance
“…Usually the small lesions are located in hypovascular subcutaneous fat, thus their growth is limited [44]. Doppler velocimetry can show intralesional vascularization if the tumor size is greater than 15 mm [44].…”
Section: Imaging Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually the small lesions are located in hypovascular subcutaneous fat, thus their growth is limited [44]. Doppler velocimetry can show intralesional vascularization if the tumor size is greater than 15 mm [44].…”
Section: Imaging Ultrasoundmentioning
confidence: 99%
“…Usually the small lesions are located in hypovascular subcutaneous fat, thus their growth is limited [44]. Doppler velocimetry can show intralesional vascularization if the tumor size is greater than 15 mm [44]. The presence of central vascularity is a highly determinative finding of malignancy for soft tissue lesions, according to Fleischer et al [45].…”
Section: Imaging Ultrasoundmentioning
confidence: 99%
“…6 The treatment of choice for abdominal wall endometriosis is the wide local excision including the adjacent fascia to achieve negative margins. 21 In cases where abdominal wall endometriosis is incorporated into the musculature of abdominal wall; it requires enbloc resection of involved myofascial elements. Histological examination reveals, foci of endometriosis composed of endometrial glands and stroma, hemosiderin pigment, fibrosis, chronic inflammation, and old hemorrhage and the presence of adipose and fibrous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Leite et al (38) The preoperative diagnosis should be confirmed by ultrasound scan of the lesion (21, 52, 59). Francica et al (21) described extensionally ultrasonographic picture of small (0,7 -2,6 cm) and large (3 -6 cm) lesions. The most typical ultrasound pattern was that of a solid nonhomogenous hypoechoic nodule with infiltrating margins, echogenic rim and increased vascularity in the musculocutaneous planes of the abdominal wall near the cesarean section incision.…”
Section: Occurrence and Diagnosticsmentioning
confidence: 99%
“…The data from these diagnostic procedures may be helpful even during planning a reconstructional operation of the abdominal wall (29, 39), though Francica et al (21) consider that they often are nonspecific.…”
Section: Occurrence and Diagnosticsmentioning
confidence: 99%